Exploring the Impact of Sibling Dynamics on Emotional and Behavioral Growth - Ningrum, Luh De Kusuma (Sinergi International Journal of Psychology, 2024)
Sibling relationships significantly influence children's cognitive, social, and emotional development, yet the complexity of these interactions requires further exploration. This study conducts a comprehensive review of existing literature to examine the role of sibling dynamics in shaping adaptive behaviors, emotional regulation, and social competence. A systematic search was performed across databases including Scopus, Google Scholar, and PubMed, utilizing keywords such as "sibling relationships," "child development," and "social-emotional growth." Inclusion criteria focused on empirical studies published within the last decade, while exclusion criteria eliminated non-empirical sources and studies outside the domains of psychology and education. Findings reveal that sibling interactions provide essential learning environments, fostering problem-solving skills, emotional resilience, and social adaptability. However, these relationships are influenced by factors such as birth order, parental involvement, socio-economic conditions, and cultural context. While positive sibling interactions enhance developmental outcomes, challenges such as rivalry and unequal parental attention pose risks. The study highlights the need for targeted interventions, including educational programs, parental guidance strategies, and policy-driven support structures to optimize sibling relationships. These findings underscore the importance of integrating sibling dynamics into broader developmental research and policy frameworks. Future studies should explore the impact of sibling loss and disability on child development and consider cross-cultural longitudinal studies to refine intervention strategies. Addressing these gaps will contribute to a more comprehensive understanding of sibling influence and inform policies that foster healthier developmental outcomes.